Closing the loop with generative AI and automated experimentation in electrochemical energy innovation. - Niu,Z; Zhao,W; Jackson,L; Cai,Q; Pinfield,VJ; Lin,W-F; Wu,B; Luo,K; Wang,Y (Sci Bull (Beijing), 2026)
Electrochemical energy technologies are central to the net-zero transition, yet their multiscale characteristics ranging from atomic materials to device architectures present critical challenges in research and development (R&D). Although artificial intelligence (AI) has accelerated discovery and design in this field, commonly used predictive AI methods remain limited in enabling disruptive advances. Generative AI has shown transformative potential in disciplines such as biology and medicine, though its impact on electrochemical energy R&D is only beginning to emerge. Here we review recent progress in applying generative AI to molecular and crystal discovery, electrode microstructure design, and system optimization, with particular attention to the role of large language models in electrochemical engineering. We argue for a paradigm shift toward generative electrochemical intelligence (GenE), a physics-informed, multimodal framework that integrates human expertise with automated experimentation. We anticipate that GenE will redefine the R&D paradigm for rapidly deployable electrochemical energy technologies and accelerate their translation into real-world applications.